Faultlines as the "Earth's Crust": The Role of Team Identification, Communication Climate, and Subjective Perceptions of Subgroups for Global Team Satisfaction and Innovation. (November 2019) - Boyraz, Maggie
Distributed teams in organizations are ubiquitous, use digital technologies extensively, and have the potential to be innovative due to the level of diversity of their members, but they face many challenges. Demographic differences can often result in the activation of team faultlines (overlap of surface-level differences), leading to formation of subgroups and negative impacts on group outcomes. This study examines the relationships between faultlines and their outcomes to discover how certain team processes mitigate the negative effects of dormant faultlines on team outcomes in globally distributed teams. The analysis of a survey of 165 global team members representing 27 teams in a multinational high-tech organization demonstrated that psychologically safe communication climate (PSCC) and team identification moderated the relationship between faultlines and perceived subgroups. Specifically, in teams with low PSCC and identification, dormant faultlines predicted an increase in perception of subgroups. The findings also indicate that perceived subgroups moderate the relationship between dormant faultlines and team satisfaction. When subgroups are less perceived by team members, faultlines predict an increase in satisfaction.